Digitalisation for Inclusive Growth in India - Rajat Sahay Dubey; Deepika; Deepa Vohra; Shivanshi Singh (International Journal of Engineering and Management Research, 2024)
India's rapid digitalization has the potential to unlock new avenues for inclusive growth, empowering marginalized communities and bridging the digital divide. This paper explores the role of digitalization in fostering inclusive growth in India, highlighting the key initiatives, challenges, and strategies for ensuring that the benefits of digital transformation reach all segments of the population. The paper examines the impact of digitalization on financial inclusion, access to healthcare and education, and the creation of employment opportunities. It also discusses the policy and regulatory frameworks necessary to create an enabling environment for inclusive digitalization, as well as the importance of digital literacy and skills development. The study proposes a multifaceted approach involving government initiatives, private sector partnerships, and community-driven interventions to harness the full potential of digitalization for inclusive growth in India. Key strategies include strengthening digital infrastructure and connectivity, promoting digital literacy and skills development, expanding digital financial inclusion, leveraging digital technologies in healthcare and education, fostering digital entrepreneurship and employment opportunities, and strengthening policy and regulatory frameworks.